2010
DOI: 10.1038/jid.2010.120
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cells Promote Fibroblast Activation via IL-1α in Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is a disorder of systemic and dermal fibrosis of uncertain etiology. Recently, we found that SSc epidermis is abnormal, taking on an activated phenotype observed during wound healing and tissue repair. As epithelial-fibroblast interactions are important during wound repair and in fibrosis in general, we investigated further the phenotype of the SSc epidermis, and tested whether the SSc epidermis provides a pro-fibrotic stimulus to fibroblasts. In this study we show that in SSc epidermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 40 publications
7
91
3
1
Order By: Relevance
“…11 Furthermore, it was showed that IL-1a plays a role in the autocrine upregulation of matrix metalloproteinase-1 (MMP-1) and tissue inhibitor of MMP-1 in normal human dermal fibroblasts stimulated by monocyte chemoattractant protein-1. 22,23 Second, in SSc patients with normal serum IL-1a levels, contracture of phalanges was significantly observed (P < 0.05). Moreover, percentage of diffusion capacity for carbon monoxide (%DLco) and arthralgia tended to be observed in SSc patients with normal serum IL-1a levels though there was no significant difference (P = 0.056, P = 0.067).…”
Section: Discussionmentioning
confidence: 95%
“…11 Furthermore, it was showed that IL-1a plays a role in the autocrine upregulation of matrix metalloproteinase-1 (MMP-1) and tissue inhibitor of MMP-1 in normal human dermal fibroblasts stimulated by monocyte chemoattractant protein-1. 22,23 Second, in SSc patients with normal serum IL-1a levels, contracture of phalanges was significantly observed (P < 0.05). Moreover, percentage of diffusion capacity for carbon monoxide (%DLco) and arthralgia tended to be observed in SSc patients with normal serum IL-1a levels though there was no significant difference (P = 0.056, P = 0.067).…”
Section: Discussionmentioning
confidence: 95%
“…Diesel exhaust nanoparticles have been shown to be internalized by monocyte-derived macrophages and keratinocytes from healthy subjects, leading to oxidative, pro-fibrotic, and pro-inflammatory processes in normal human skin [71,72]. A recent series has demonstrated that diesel exhaust nanoparticles induced, in vitro, (1) higher mRNA gene expression of metalloproteases 2, 7, 9, and 12; collagen I and III; and vascular endothelial growth factor (VEGF) in SSc fibroblasts than in controls and (2) activation of keratinocytes of patients with diffuse cutaneous SSc with increase of pro-fibrotic cytokines: IL-1α, IL-8, and IL-6 mRNA levels [73]. IL-1α has been reported to be greatly increased in SSc epidermis, and it is speculated to initiate keratinocyte-fibroblast interactions, leading to fibroblast activation [74].…”
Section: Air Pollutantsmentioning
confidence: 97%
“…Fibrosis is a hallmark of many connective tissue diseases, including scleroderma and systemic sclerosis (reviewed by Ihn 2005;Krieg et al 2007;Olson and Soriano 2009). One of the factors expressed by keratinocytes that promotes fibroblast activation in systemic sclerosis is IL1-a (Aden et al 2010).…”
Section: Fibrosismentioning
confidence: 99%